MADRASAH PADA MASA ISLAM KLASIK: Analisis Historis atas Metode yang Digunakan - Hasaruddin, Hasaruddin (Hunafa: Jurnal Studia Islamika, 2011)
Abstract: The Institute of Islamic education is foremost on the classic era is the mosque. However, because of the demands of Muslim society to education has increased and the demands of the welfare of the teachers have also increased the education that was originally held in the mosque developing into education held at the madrasah. Therefore, madrasah educational institutions were Â the development of the mosque, the mosque khan then increased to madrasah. Learning methods used in the madrasah also experienced growth. The method of learning at the madrasah Â such as Â al-samÄ' (dictation), and al-ijÄzah (diploma) was not found in the learning in the mosqueKata Kunci: madrasah, masa Islam klasik, metode pengajaran